The Rural Social Enterprise and its Contribution to the Conservation of Amaranth as an Agrifood Heritage, Case Study: Centéotl, A.C. Zimatlán, Oaxaca, Mexico - Hernandez-Hernández, Beatriz Rebeca; Regino-Maldonado, Juan; Miguel-Velasco, Andrés Enrique (Revista de Estudios Andaluces, 2020)
This article describes the activities carried out by the rural social enterprise, Centéotl A. C. in Zimatlán, Oaxaca, Mexico. To promote the conservation of amaranth cultivation as an agrifood heritage. The methodology is qualitative and descriptive. The analysis by means of the statistical package SPSS v.25 determined the frequency of affirmative answers with more than 50 percent, to specify a positive impact. The results showed that goods offered by the company contribute to the continuity of the crop (81,08 percent), and to a lesser extent services offered by Bancomunidad (51,3 percent). This case study shows that through production and consumption techniques this food can be adopted in the daily diet. It is concluded that the activities carried out by Centéotl promote the recognition of this crop as an agrifood heritage.